(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2019)
“The microbial diversity and structure in peat land forest in Indonesia”, DOI: https://doi.org/10.3329/jbcbm.v5i1.42193 in the ‘Journal of Biodiversity Conservation and Bioresource Management (JBCBM)’ Vol. 5(1)-June’ 2019 did not follow the ‘Instructions to Contributors’ of the JBCBM properly. Accordingly, corresponding author confessed it in a statement; and sent the statement to the Editor-in-Chief of the Journal. He apologized and applied to withdraw the article from the JBCBM. As per rules and regulations of the Journal, the authority of JBCBM recommends to retreat the article from the JBCBM.